Assessment of Service Quality of Sinabang Ferry Port Based on Sinabang - Calang Route Users’ Perception - Miranti Alpina; Yusria Darma; Cut Dwi Refika; Mubarak Mubarak; Ahyin Bilhuda Dasopang; Faiza Mauladea; Suhana Koting (Popular Scientist, 2026)
Sinabang Ferry Port serves as a vital transportation hub connecting Simeulue Island with the mainland Sumatra, especially in serving remote and underdeveloped areas. As passenger traffic increases, evaluating service quality becomes crucial to support port management improvements and increase user satisfaction. This study aims to analyze the level of service at Sinabang Ferry Port based on user satisfaction and identify service attributes that need to be prioritized for quality improvement. The data were analyzed using the Importance Performance Analysis (IPA) method with five dimensions of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. The number of respondents was set at 156 people using the Slovin formula based on the average weekly number of passengers. The results showed that the level of user satisfaction with Sinabang Ferry Port services obtained an average level of suitability (LoS) score of 85,13%, indicating that user may dissatisfaction with port services and the need for improvements. The attributes that need to be prioritized (Quadrant I) include facilities for people with disabilities, pregnant women, and the elderly, information about terminal layout, departures and arrivals, and the availability of security equipment, such as CCTV. Furthermore, the tangibles, reliability, and assurance dimensions require significant attention to enhance service quality. These results provide essential insights for port authorities in formulating targeted and sustainable strategies to strengthen ferry service management and support regional accessibility.